Signage Design “Fuadah” as An Effort to Unify Diversity in Salatiga - Dwijayanti, Ita (Islah: Journal of Islamic Literature and History, 2023)
As the only state university in Salatiga, Universitas Islam Negeri (UIN) Salatiga strives to be a reference laboratory for moderate Islamic Studies in Salatiga as well as Indonesia. Although UIN Salatiga has a faculty that specializes in moderate Islam, named Faculty of Ushuluddin, Adab, and Humanities (FUADAH), the data shows that only 11% of students over 5 other faculties are interested and study there. The preliminary study done by the researcher implies the lack of socialization in the form of signage design for branding. This research aims to present and explain a "FUADAH" signage design idea using the architectural scientific approach in the realm of religious science and moderate Islam. In designing the signage, some academicians participate and give ideas by using an online form distributed by the researchers. The result of this study is a signage design and logos of FUADAH.